A dicopper(i)-dimesoionic carbene complex as a click catalyst: mechanistic implications. Issue 24 (30th May 2019) - Beerhues, Julia; Fauché, Kevin; Cisnetti, Federico; Sarkar, Biprajit; Gautier, Arnaud
Abstract : A dicopper(i ) complex comprising a dimesoionic carbene and an acetate-bridge is synthesized and fully characterized. Abstract : A dicopper(i ) complex comprising a dimesoionic carbene and an acetate-bridge is synthesized and fully characterized. This complex is a potent pre-catalyst for the azide–alkyne cycloaddition reaction. A full kinetic investigation shows a first order in azide and a catalyst order smaller than one due to an equilibrated dimerization of the catalyst.